Japanese Buddhism in Europe - Borup, Jørn; Porcu, Elisabetta (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026, 2025)
Japanese Buddhism in Europe focuses on religious circulation between Japan and Europe. Through an exploration of a variety of Buddhist traditions in different European countries the volume illustrates the trajectories of Japanese Buddhism and its dynamics of acculturation both in a historical and contemporary perspective.